Pediatric Gastrointestinal Endoscopic Sedation: A 2010 Nationwide Survey in Taiwan - Po-Hon Chen; Tzee-Chung Wu; Chih-Yu Chiu (Elsevier, 2012)
There is insufficient data on pediatric endoscopic sedation practices worldwide. This study aimed to assess nationwide data on the current pediatric endoscopic sedation practices in Taiwan. Methods: Members of the Taiwan Society of Pediatric Gastroenterology Hepatology and Nutrition in 2010 were asked to participate in an 18-item questionnaire survey regarding current sedation practices for diagnostic esophagogastric-duodenoscopy (EGD). Results: A total of 22 of 32 questionnaires were returned for a response rate of 68.8%. A majority (86.4%) of the respondents practiced in a medical center hospital setting, and 72.7% preferred sedation during EGD. The proportions of respondents applying sedative methods in cases aged < 1, 1∼12, and > 12 years old were 85.7%, 100%, and 23.7% respectively. Ketamine (27.8%) and midazolam with meperidine (22.2%) were the most commonly applied sedation agents, while the percentage of respondents using regimens that included propofol was 11.2%. Comparing complications between EGD with and without sedation, only hypoxia (Wilcoxon statistics=347.00, p=0.003) was significantly more common in sedated patients. The endoscopists' satisfaction rating was greater among respondents using sedation compared to those without (visual analog scale 9 vs. 7; p=0.0001). Conclusion: A majority of pediatric EGD in Taiwan was performed under sedation and applied more often to younger children. Endoscopists were more satisfied during EGD when practicing sedation. This survey should help formulate updated practice guidelines and policies regarding endoscopic sedation.